2021
DOI: 10.52547/jcbr.5.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Ineffective Attitudes and General Health in Patients with Chronic Renal Disease Undergoing Hemodialysis in a Hospital in Gorgan, Iran

Abstract: Background and objectives: Chronic kidney disease (CKD) is a major public health problem worldwide. Hemodialysis (HD) is the most common method of treating CKD. Dysfunctional attitudes play a major role in cognitive vulnerability and general health of HD patients. The aim of this study was to investigate relationship between dysfunctional attitudes and general health of patients with CKD undergoing HD. Methods: This cross-sectional study was performed on CKD patients undergoing HD at a hospital in Gorgan, Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In line with these findings, Sheikh Ahmadi et al did not observe a significant correlation between parents' education levels and adolescent anxiety (21). Similarly, Derakhshanpour et al found no correlation between anxiety and the type of school attended (13). Additionally, in a study by Latifnejad et al, similar to the present study, no significant correlation was observed between puberty and students' anxiety levels (22).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In line with these findings, Sheikh Ahmadi et al did not observe a significant correlation between parents' education levels and adolescent anxiety (21). Similarly, Derakhshanpour et al found no correlation between anxiety and the type of school attended (13). Additionally, in a study by Latifnejad et al, similar to the present study, no significant correlation was observed between puberty and students' anxiety levels (22).…”
Section: Discussionsupporting
confidence: 78%
“…In this context, Derakhshanpour et al reported a 14.5% prevalence of anxiety disorders among 745 primary school children in Gorgan (13). Khaleghi et al found that out of 2095 children and adolescents aged 6 to 18 years in urban areas of Tehran, the overall prevalence of psychiatric disorders was 28.2%, with anxiety disorders being the most common at 21.9% (14).…”
Section: Discussionmentioning
confidence: 99%